2012
DOI: 10.3109/19401736.2012.726619
|View full text |Cite
|
Sign up to set email alerts
|

Migration route estimation of the Jeju striped field mouseApodemus agrarius chejuensis(Rodentia, Muridae)

Abstract: The taxonomic relationship between two Korean field mice species, Apodemus agrarius coreae and A. a. chejuensis, as well as their possible historic migration routes, was examined by molecular genetic analysis of the complete mitochondrial cytochrome b gene of 73 mice collected from the Korean Peninsula and Jeju Island. Our findings suggest that A. a. coreae and A. a. chejuensis populations expanded and dispersed rapidly. Bayesian and network analysis showed that A. a. chejuensis is a clearly distinct populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…15 haplotypes from China and South Korea have not been assigned to any group. The two most differentiated groups have been formed by the populations from the Jeju and Taiwan Islands (Group 2 and Group 4), whose evolutionary history has been reviewed in detail previously [9,17]. The other six haplogroups (Group 1, 3, 5-8) have been represented by mainland populations, indicating a more complex genetic structure A. agrarius than recent studies have shown [18].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…15 haplotypes from China and South Korea have not been assigned to any group. The two most differentiated groups have been formed by the populations from the Jeju and Taiwan Islands (Group 2 and Group 4), whose evolutionary history has been reviewed in detail previously [9,17]. The other six haplogroups (Group 1, 3, 5-8) have been represented by mainland populations, indicating a more complex genetic structure A. agrarius than recent studies have shown [18].…”
Section: Discussionmentioning
confidence: 97%
“…By now, a considerable amount of data on the genetic differentiation, phylogeography, and evolutionary history of A. agrarius has been obtained by analyzing the mitochondrial genome. The phylogenetic relations of continental and island populations of South Korea [7][8][9], the genetic diversity of populations of the Russian Far East and isolated populations in the Far North (Magadan Region) [10,11], and the history of colonization of the Danish islands by striped field mouse [12] have all been studied this way. Hypotheses regarding the time, consecutiveness and the possible causes of intraspecific genetic differentiation and the history of the formation of the modern A. agrarius range have been proposed based on cytochrome b gene data [10,11,[13][14][15][16][17], which have been confirmed in a recent work involving significant amount of material from both parts of the species distribution area [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ancestral population of A . chejuensis on Jeju Island may have originated from the Korean peninsula or eastern China [ 35 ]. Han et al and Koh et al estimated the population of A .…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, four subspecies ( A. a mantchuricus, A. a. chejuensis, A. a. pallenscens , and A. a. coreae ) have been reported, but only A. a. chejuensis on Jeju Island has a definitive geographic barrier from the other subspecies [ 3 ]. Based on differences in morphology [ 4 – 7 ], physiology [ 8 ], and mitochondrial DNA [ 9 – 11 ], the taxonomic status of A. a. chejuensis has changed frequently in rank between species and subspecies. The striped field mouse is the first known vector of Hanta virus, which killed roughly 3000 United Nations soldiers per year during the Korean War, which has attracted great attention by epidemiologists [ 12 ].…”
Section: Introductionmentioning
confidence: 99%